2011
DOI: 10.1104/pp.110.169797
|View full text |Cite
|
Sign up to set email alerts
|

Organelles Contribute Differentially to Reactive Oxygen Species-Related Events during Extended Darkness      

Abstract: Treatment of Arabidopsis (Arabidopsis thaliana) leaves by extended darkness generates a genetically activated senescence program that culminates in cell death. The transcriptome of leaves subjected to extended darkness was found to contain a variety of reactive oxygen species (ROS)-specific signatures. The levels of transcripts constituting the transcriptome footprints of chloroplasts and cytoplasm ROS stresses decreased in leaves, as early as the second day of darkness. In contrast, an increase was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 72 publications
3
72
0
Order By: Relevance
“…Perturbation of mitochondrial metabolism can result in production of superoxide and H 2 O 2 (Noctor et al, 2007;Miller et al, 2010). It was recently shown that mitochondria and peroxisomes work in a successive manner generating oxidative signals in response to the induction of senescence (Rosenwasser et al, 2011). Consistent with this, it is of interest that mitochondrial mutants of alternative oxidase activity are negatively regulated with many of the stresses (see AS-Aox1 and TDNA-Aox1; Fig.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Perturbation of mitochondrial metabolism can result in production of superoxide and H 2 O 2 (Noctor et al, 2007;Miller et al, 2010). It was recently shown that mitochondria and peroxisomes work in a successive manner generating oxidative signals in response to the induction of senescence (Rosenwasser et al, 2011). Consistent with this, it is of interest that mitochondrial mutants of alternative oxidase activity are negatively regulated with many of the stresses (see AS-Aox1 and TDNA-Aox1; Fig.…”
Section: Discussionmentioning
confidence: 64%
“…The actual maximum correlation value and signal size is assembled in Supplemental Table S1 and ranged from 0.62 for 1 h OG application to a high of 0.85 for 309 flg22 treatment. Such correlation values can be considered highly significant (Volodarsky et al, 2009;Rosenwasser et al, 2011Rosenwasser et al, , 2013 and point to the involvement of a singlet oxygen-like signature in those data sets.…”
Section: Singlet Oxygen Generates a Transcriptome Footprint In Many Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is possible to determine the redox potential of the glutathione pool in a high spatial and temporal resolution using various redox-sensitive green fluorescent proteins (for example roGFP) encoded in the test plant. The method requires transient or permanent plant transformation and has already been used in many cases (Beneloujaephajri et al, 2013;Heller et al, 2012;Jubany-Mari et al, 2010;Lehmann et al, 2009;Rosenwasser et al, 2011).…”
Section: Detection Of Rosmentioning
confidence: 99%